ANALYSIS OF DIGITAL MARKETING STRATEGY AND GOVERNMENT SUPPORT TOWARDS THE IMPROVEMENT OF THE CREATIVE ECONOMY IN DESTINATIONS LAKE TOBA TOURISM - Bunga Aditi (RADJA PUBLIKA, 2025)
The increase in the creative economy provides an overview of business growth, especially local business actors in the Lake Toba Tourist Destination, so there needs to be a better marketing strategy, especially utilizing digital marketing to expand information and provide an overview of the conditions in the tourist destination, then government support is also needed to socialize the creative economy business process so that these business actors can be directed towards the sustainability of the regional business. The purpose of this study is to examine and analyze digital marketing strategies and government support for increasing the creative economy in the Lake Toba Tourist Destination. The results of the study show that digital marketing has a significant effect on government support. Government support has a significant effect on increasing the creative economy. Government support as an intervening variable has a significant impact on increasing the influence of digital marketing on increasing the creative economy.